Synthesis and Characterization of Polyesteramide Hot Melt Adhesive from Low Purity Dimer Acid, Ethylenediamine, and Ethanolamine. (7th April 2014) - Kadam, Pravin G.; Vaidya, Parth; Mhaske, Shashank T.
Abstract : Polyesteramide hot melt adhesive (HMA) was synthesized using low purity dimer acid (composition: 3% linoleic acid, 75% dimer acid, and 22% trimer acid), ethanolamine, and ethylenediamine. Ethanolamine was added as a partial replacement (10, 20, and 30%) of ethylenediamine. Prepared HMAs were characterized for acid value, amine value, hydroxyl value, Fourier transform infrared spectroscopy, mechanical (tensile strength, percentage strain at brea, and shore D hardness), thermal (glass transition temperature, melting temperature, enthalpy of melting, crystallization temperature, and enthalpy of crystallization), rheological (viscosity versus shear rate and viscosity versus time), and adhesion properties (T-peel strength and lap shear strength). Replacement of ethylenediamine by ethanolamine replaced certain amide linkages by ester linkages, decreasing the intermolecular hydrogen bonding, leading to decrease in the crystallinity of the material, and thus the mechanical, thermal, adhesion, and rheological properties. However, HMAs prepared using ethanolamine will have better low temperature flexibility due to low glass transition temperature and better adhesion process due to the lower viscosity.